Outsourcing diagnostics in public hospitals: boon or bane! Insights from Punjab’s public-private partnerships experience - Preet, Amrit; Bharti,; Attri, Ritu (International Journal Of Community Medicine And Public Health, 2026)
The outsourcing of diagnostic services through public-private partnerships (PPPs) has emerged as a policy tool to address infrastructure and manpower gaps in India’s public health sector. Punjab’s Civil Hospital Mohali recently adopted this model, contracting a private provider to deliver advanced diagnostic services including MRI, CT, ultrasonography, and laboratory investigations. Drawing on data collected between December 2021 to February 2022, as part of the developing confident and critical thinkers case study writing program facilitated by the Mahatma Gandhi State Institute of Public Administration (MGSIPA) and the Chandler Institute of Governance (CIG), Singapore, this paper critically examines the outcomes of the PPP model. Early results suggest improved access, affordability, and efficiency. However, concerns related to equity, medical education, and sustainability have also surfaced. This commentary weighs the benefits and pitfalls of outsourcing diagnostics in public hospitals and highlights lessons for health policy and governance.